2020
DOI: 10.1002/1878-0261.12621
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH and DNA repair pathways are more frequently targeted by genomic alterations in inflammatory than in non‐inflammatory breast cancers

Abstract: Inflammatory breast cancer (IBC) is the most pro‐metastatic form of breast cancer. Better understanding of its pathophysiology and identification of actionable genetic alterations (AGAs) are crucial to improve systemic treatment. We aimed to define the DNA profiles of IBC vs noninflammatory breast cancer (non‐IBC) clinical samples in terms of copy number alterations (CNAs), mutations, and AGAs. We applied targeted next‐generation sequencing (tNGS) and array‐comparative genomic hybridization (aCGH) to 57 IBC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 53 publications
(98 reference statements)
5
36
1
Order By: Relevance
“…Genes involved in DNA repair were found more frequently altered in IBC than in non-IBC breast cancer [36]. TP53 was found to be the most frequently altered gene in IBC and its rate of mutation in IBC was found to be significantly higher than in non-IBC patients [36][37][38]. Matsuda et al found that TP53 was altered in 75% of IBC (18/24 patients) and in 28.2% (106/376 patients) of non-IBC patients [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes involved in DNA repair were found more frequently altered in IBC than in non-IBC breast cancer [36]. TP53 was found to be the most frequently altered gene in IBC and its rate of mutation in IBC was found to be significantly higher than in non-IBC patients [36][37][38]. Matsuda et al found that TP53 was altered in 75% of IBC (18/24 patients) and in 28.2% (106/376 patients) of non-IBC patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…Deficient DNA repair and control of cell cycle would contribute to disease progression. In a recent study of 101 untreated primary IBC tumors aggregated from four public datasets, Bertucci et al showed that the genomic profile of IBC is different from non-IBC breast cancer [36]. Genes involved in DNA repair were found more frequently altered in IBC than in non-IBC breast cancer [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rarity of the disease, misdiagnosis, and difficulty in sample collection before treatment have resulted in a limited number of published molecular studies [ 2 , 5 , 9 , 10 ]. Transcriptome profiling analyses revealed that IBC is highly heterogeneous, showing the same molecular subtypes of non-IBC, with a higher proportion of HER2-positive and triple-negative (TNBC: negativity for estrogen receptor: ER, progesterone receptor: PR, and HER2) subtypes [ 2 , 5 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Copy number alterations (CNAs) have been reported in a few studies using both low-resolution techniques (such as restriction fragment length polymorphism or microsatellite markers) and more robust methodologies (array-comparative genomic hybridization and next-generation sequencing (NGS) [ 10 , 14 , 15 , 16 , 17 , 18 ]. CNA data also failed in distinguishing IBC from non-IBC cases.…”
Section: Introductionmentioning
confidence: 99%